Synthesis of α,α-diaryl nitriles by radical nucleophilic substitution - Tempesti, Tomas Cristian (2012)
The present study shows that the anion of 2-naphthylacetonitrile is substituted selectively at its Cα by aromatic halides, through a radical nucleophilic substitution mechanism, to give the corresponding α,α-diaryl nitriles in good yields. The regioselectivity of this ambident nucleophile changes with the steric hindrance at the radical centre from the aromatic substrate. The selectivity observed was investigated through a computational model of the key reaction step. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2012.